Educational Content Based on Competency Approach in Primary Class Education Lessons - Dilova Nargiza Gaybullayevna; Hakimova Nargiza Supkhanovna (Researchparks Publishing, 2022)
the article describes the competence approach in education, its importance and relevance, the uniqueness of the educational process based on the competence approach in primary grades. In the content of education science, scientific-theoretical considerations about the importance of language knowledge, in-depth study of folklore, formation of necessary life skills in students, and formation of social-legal competences in their minds from the early school age are highlighted.